What Happens Between Depositional Events, Stays Between Depositional Events: The Significance of Organic Mat Surfaces in the Capture of Ediacara Communities and the Sedimentary Rocks That Preserve Them - Droser, Mary L.; Evans, Scott D.; Tarhan, Lidya G.; Surprenant, Rachel L.; Hughes, Ian V.; Hughes, Emmy B.; Gehling, James G. (Frontiers in Earth Science, 2022)
In the absence of complex, bioturbating organisms, the seafloor during the Precambrian was covered in widespread organic matgrounds. The greatest diversity and complexity of organic mat textures occur in the Ediacaran fossil record as exemplified by the Ediacara Member of the Rawnsley Quartzite cropping out in and around the Flinders Ranges, South Australia. This succession unambiguously demonstrates that heterogenous mats coexisted with and were central to the ecology and biology of the Ediacara Biota. Excavation of 33 fossiliferous beds with varying degrees of mat development provide the opportunity to utilize this record to develop criteria to evaluate the maturity or extent of growth of Ediacaran matgrounds and, using these characteristics, to examine the relationship between mat type, mat maturity and Ediacara Biota community structure. Based on the assumption that mat maturity represents an indicator of the duration of time between burial events, we can test predictions about the relationship between mat maturity and community development. We find that mat maturity, rather than the mat type itself, more strongly influenced the distribution of taxa and the development of Ediacara macroorganism communities. Using a ranked mat maturity index, we find that density of macroscopic body fossils and genus diversity correlate with mat maturity, evenness however, does not. We additionally find that the sessile taxa Obamus and Coronacollina are restricted to surfaces with mature mats while all other Ediacaran macrobiota show no connection to occurrence and mat maturity. However, we do observe that large Dickinosnia are more likely to be on mature mat surfaces. The exceptional record of mat surfaces preserved in the Flinders Ranges area demonstrates that, in addition to the apparent ecological role played by mat surfaces in Ediacaran communities, they were also likely a significant component of the Ediacara Member biomass and were integral to community function.